Transient Pancytopenia and Granulocyte Abnormalities After Suicide Attempt With Colchicine in a Patient With Familial Mediterranean Fever. Issue 6 (August 2019) - Baysal, Birsen; Tüfekçi, Özlem; Erdem, Melek; Yilmaz, Şebnem; Ören, Hale
Abstract : Supplemental Digital Content is available in the text.